Dismantling the Relationship between Kiai and Santri: A Critical Review of the Social and Cultural Dynamics of Pesantren in East Java - Achmadin, Balya Ziaulhaq; Asrori, Mohammad; Barizi, Ahmad; Haris, Abd.; Fattah, Abdul (IAIN Pontianak, 2024)
This study aims to reveal the dynamics of the relationship between Kiai and santri in traditional pesantren. This research deconstructs the relationship between Kiai and Santri in the Indonesian socio-cultural context. Through a critical approach, this research examines the dynamics of power and cultural influences that color the relationship. Using a case study, this research reveals the complexity of the Kiai and Santri relationship that goes beyond the traditional teacher-student relationship. The research aims to unpack the assumptions underlying this traditional relationship, as well as reveal the power structures and cultural dynamics that exist. Through qualitative methods, data was collected from in-depth interviews, participatory observation, and document analysis. The results show that the relationship between Kiai and Santri in traditional pesantren is built on the basis of strong religious and cultural values. Kiai holds a central role as a spiritual leader and teacher, while Santri places themselves as obedient and respectful students. This relationship is characterized by a clear hierarchy, where Kiai has great authority and influence over both Kiai and santri. Then the relationship between Kiai and Santri is not only hierarchical, but also complex and dynamic, with the negotiation and resistance of santri to the kiai's authority. Santri, who are often positioned in subordinate power (Patron-Client), demonstrate the ability to negotiate their identity and space within the pesantren structure. This research highlights the importance of understanding this relationship in the broader context of social and cultural change, and encourages the reconstruction of a more equal relationship between kiai and santri. The findings contribute to the study of Islamic education and social dynamics in Indonesia, and open space for discussion on the redefinition of Kiai according to relevant pesantren education reviews.